PENGGUNAAN VIDEO ANIMASI PEMBELAJARAN FIKIH DALAM MEMBANGUN MOTIVASI BELAJAR SISWA DI MIS AL HIKMAH BOJONGSARI DEPOK - Miftakhul Ilmi Mustofa; Sa'diyah (STKIP Subang, 2026)
The research problem lies in the teaching and learning process, specifically low learning outcomes, students’ lack of understanding of fiqh, and low student motivation to learn; consequently, teachers need an animated video to optimize teaching and learning activities. This study aims to examine the teaching of fiqh through the use of animated videos in building student motivation at MIS Al-Hikmah Bojongsari, Depok. This study employs a qualitative approach using a descriptive method. Primary data were collected from the Fiqh teacher, while secondary data were obtained from interviews and document analysis conducted at MIS Al-Hikmah. Data analysis employed the Miles and Huberman flow method, comprising three stages: (1) Data Reduction, (2) Data Presentation, and (3) Drawing Conclusions. Data collection was conducted through interviews, observations, and documentation. The research results indicate that the use of animated videos effectively builds students’ motivation to learn, enables students to understand abstract and complex material, and increases student engagement during the learning process. Additionally, the use of animated videos helps students remember and understand Fiqh concepts better, resulting in better outcomes than conventional methods. This study emphasizes the importance of careful planning and teacher creativity in integrating animated video media to make learning more engaging and effective.